2015
DOI: 10.3390/md13085016
|View full text |Cite
|
Sign up to set email alerts
|

Eribulin in Cancer Treatment

Abstract: Halichondrin B is a complex, natural, polyether macrolide derived from marine sponges. Eribulin is a structurally-simplified, synthetic, macrocyclic ketone analogue of Halichondrin B. Eribulin was approved by United States Food and Drug Administration in 2010 as a third-line therapy for metastatic breast cancer patients who have previously been treated with an anthracycline and a taxane. It has a unique microtubule dynamics inhibitory action. Phase III studies have either been completed or are currently ongoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 95 publications
0
36
0
Order By: Relevance
“… 111 113 In this regard, eribulin has been found to be especially efficacious in patients with tumours harbouring beta-tubulin mutations that are refractory to taxanes. 114 , 115 In preclinical models, eribulin was shown to induce an irreversible mitotic arrest, apoptosis and tumour regression in multiple cancer cell lines with a mean IC50 that is 2–4-fold more potent than vinblastine and paclitaxel. 114 , 116 , 117 A broad range of sarcoma cell lines, including liposarcoma, leiomyosarcoma, Ewing’s sarcoma, synovial sarcoma and fibrosarcoma, have been demonstrated to be sensitive to eribulin.…”
Section: Systemic Control In Sarcomamentioning
confidence: 99%
“… 111 113 In this regard, eribulin has been found to be especially efficacious in patients with tumours harbouring beta-tubulin mutations that are refractory to taxanes. 114 , 115 In preclinical models, eribulin was shown to induce an irreversible mitotic arrest, apoptosis and tumour regression in multiple cancer cell lines with a mean IC50 that is 2–4-fold more potent than vinblastine and paclitaxel. 114 , 116 , 117 A broad range of sarcoma cell lines, including liposarcoma, leiomyosarcoma, Ewing’s sarcoma, synovial sarcoma and fibrosarcoma, have been demonstrated to be sensitive to eribulin.…”
Section: Systemic Control In Sarcomamentioning
confidence: 99%
“…Eribulin is currently approved in more than 60 countries for the treatment of refractory breast cancers and liposarcomas. In a series of preliminary preclinical experiments, eribulin showed anticancer activities in diverse cancer cell lines, including a GBM cell line . In this study, we investigated the efficacy of eribulin in inhibiting GBM cell proliferation in vitro and in vivo , as well as the pharmacokinetics of eribulin in a mouse harboring intracerebrally‐transplanted human GBM cells.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of preliminary preclinical experiments, eribulin showed anticancer activities in diverse cancer cell lines, including a GBM cell line. [27][28][29] In this study, we investigated the efficacy of eribulin in inhibiting GBM cell proliferation in vitro and in vivo, as well as the pharmacokinetics of eribulin in a mouse harboring intracerebrally-transplanted human GBM cells. Our results showed that eribulin is active against GBM with TERT promoter mutations and penetrated mouse brain tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Eribulin was responsible for prolonging overall survival (OS) of heavily pretreated metastatic breast cancer patients in a large Phase III trial ( Cortes et al , 2011 ) and is now under clinical development in earlier settings such as neoadjuvant and adjuvant settings. Furthermore, its unique mechanism of action and the absence of cross-resistance with taxanes have led to the design of clinical trials in multiple indications including: bladder, lung and prostate cancers ( Polastro et al , 2014 ; Swami et al , 2015 ). On the basis of the promising results from the phase II ( Schöffski et al , 2011 ), a randomised, open-label, multicenter phase III trial of eribulin mesylate in patients with locally advanced or recurrent and/or metastatic adipocytic sarcoma or leiomyosarcoma was conducted (NCT01327885).…”
Section: Discussionmentioning
confidence: 99%